Stress leads to prosocial action in immediate need situations - Buchanan, Tony W.; Preston, Stephanie D. (Frontiers in Behavioral Neuroscience, 2014)
Stress clearly influences decision making, but the effects are complex. This review focuses on the potential for stress to promote prosocial decisions, serving others at a temporary cost to the self. Recent work has shown altruistic responses under stress, particularly when the target’s need is salient. We discuss potential mechanisms for these effects, including emotional contagion and offspring care mechanisms. These neurobiological mechanisms may promote prosocial—even heroic—action, particularly when an observer knows the appropriate response and can respond to a target in need. The effects of stress on behavior are not only negative, they can be adaptive and altruistic under conditions that promote survival and well-being at the individual and group level.